2022
DOI: 10.3390/ph16010026
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Encapsulated Resveratrol as an Anti-Aging Agent to Delay Cataract Development

Abstract: Nanoparticle-based drug delivery systems, which can overcome the challenges associated with poor aqueous solubility and other harmful side effects of drugs, display potent applications in cataract treatment. Herein, we designed a nanosystem of gold nanoparticles containing resveratrol (RGNPs) as an anti-aging agent to delay cataracts. The spherical RGNPs had a superior ability to inhibit hydrogen peroxide-mediated oxidative stress damage, including reactive oxygen species (ROS) production, malondialdehyde (MDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Gold nanoparticles (AuNPs) have been used in previous medical studies due to their ease of functionalisation with various active molecules [ 20 ]. A recent study [ 21 ] demonstrated significant uptake of AuNPs functionalised with resveratrol, a stilbene from the subclass of dietary polyphenols, in ocular lens epithelial cells, in both in vitro and in vivo models of CA, with no dose-dependent toxicity. Similarly, improvements were demonstrated in a Wistar rat model of diabetic retinopathy when treated with AuNPs phytoreduced with resveratrol [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles (AuNPs) have been used in previous medical studies due to their ease of functionalisation with various active molecules [ 20 ]. A recent study [ 21 ] demonstrated significant uptake of AuNPs functionalised with resveratrol, a stilbene from the subclass of dietary polyphenols, in ocular lens epithelial cells, in both in vitro and in vivo models of CA, with no dose-dependent toxicity. Similarly, improvements were demonstrated in a Wistar rat model of diabetic retinopathy when treated with AuNPs phytoreduced with resveratrol [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles (AuNPs) have been used in previous medical studies due to their ease of functionalisation with various active molecules [20]. A recent study [21] demonstrated significant uptake of AuNPs functionalised with resveratrol, a stilbene from the subclass of dietary polyphenols, in ocular lens epithelial cells, in both in vitro and in vivo models of CA, with no dosedependent toxicity. Similarly, improvements were demonstrated in a Wistar rat model of diabetic retinopathy when treated with AuNPs phytoreduced with resveratrol [22].…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol, a stilbene derivative, is a natural nutrient in grapes, which possesses many biological characteristics, such as anti-inflammatory, neuroprotective, anti-cancer, anti-oxidative, and anti-diabetic effects [ 11 , 12 , 13 ]. In recent years, the anti-aging potential of resveratrol has been one of the most eye-catching biological activities [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Resveratrol is a potential candidate as an anti-aging agent, which can exert its anti-aging and health benefits via anti-oxidative, calorie-restrictive, and anti-inflammatory effects through activating the nuclear factor erythroid 2-related factor 2 (Nrf2), sirtuin 1 (Sirt1), and AMP-activated protein kinase (AMPK) signaling pathways.…”
Section: Introductionmentioning
confidence: 99%